The Toxoplasma nuclear factor TgAP2XI‐4 controls bradyzoite gene expression and cyst formation. Issue 3 (26th December 2012) - Walker, Robert; Gissot, Mathieu; Croken, Matthew M.; Huot, Ludovic; Hot, David; Kim, Kami; Tomavo, Stanislas
Summary Toxoplasma gondii undergoes many phenotypic changes during its life cycle. The recent identification of AP2 transcription factors in T. gondii has provided a platform for studying the mechanisms controlling gene expression. In the present study, we report that a recombinant protein encompassing the TgAP2XI‐4 AP2 domain was able to specifically bind to a DNA motif using gel retardation assays. TgAP2XI‐4 protein is localized in the parasite nucleus throughout the tachyzoite life cycle in vitro, with peak expression occurring after cytokinesis. We found that the TgAP2XI‐4 transcript level was higher in bradyzoite cysts isolated from brains of chronically infected mice than in the rapidly replicating tachyzoites. A knockout of the TgAP2XI‐4 gene in both T. gondii virulent type I and avirulent type II strains reveals its role in modulating expression and promoter activity of genes involved in stage conversion of the rapidly replicating tachyzoites to the dormant cyst forming bradyzoites. Furthermore, mice infected with the type II KO mutants show a drastically reduced brain cyst burden. Thus, our results validate TgAP2XI‐4 as a novel nuclear factor that regulates bradyzoite gene expression during parasite differentiation and cyst formation.